EFFEKTIVITAS MIKROKAPSUL OLEORESIN FULI PALA (Myristica fragrans HOUTT) SEBAGAI PENGAWET DAGING AYAM BROILER - Alston Millan (Jurnal Teknologi & Industri Hasil Pertanian, 2020)
Nutmeg oleoresin microcapsule is the solid, liquid, and gas coating technology of the nutmeg fruit.  The purpose of this study was to know how mace nutmeg oleoresin microcapsules could preserve the broiler chicken meat at room temperature during 4 days of observation. The experimental design used was a Completely Randomized Design (CRD) consisting of 5 treatments with mace concentration of nutmeg microcapsules oleoresin (0, 50, 100, 150, and 200) ppm. The variables observed were water content, pH value, total microbes, and organoleptic properties (color, aroma, and texture). The results showed that mace nutmeg oleoresin microcapsules did not affect (p> 0.05)  water content and sensory properties of broiler chicken meat, but had a significant effect (p <0.05) on the pH value and total microbe at the same day of room temperature storage. Panel organoleptic test results on the level of preference for meat color, aroma, and texture of chicken meat were in the range score of 3 (somewhat like) to 4 (somewhat dislike). The treatments of nutmeg oleoresin did not affect (p> 0.05) on color, the aroma, and the texture of broiler chicken meat. This research shows that marinating using oleoresin microcapsules has not been effective as a preservative to broiler chicken meat at room temperature. Keywords: chicken meat, mace nutmeg oleoresin microcapsules